THE EUROPEAN SOURCE OF GUNNERY PRACTICAL KNOWLEDGE IN KITĀB AL-ʿIZZ WA AL-MANĀFIʿ LI AL-MUJĀHIDĪN FĪ SABĪL ALLĀH BI AL-MADĀFIʿ - Mansour Mohamed Sabri; Khairil Husaini Jamil; Ahmed Jomaa Abd Al-Hamid, (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2022)
The Arabic manuscripts are known for their historical role as dynamic tools for restoring Muslim's historical identity and records. It covers a wide range of areas and fields, including military technology. The military engineer Captain Ibrāhīm ibn Aḥmad ibn Muḥammad ibn Ghānim ibn Zakariyyā al-Andalusī (d. 1641 AD) produced a remarkable well-illustrated encyclopaedic book in 1632 AD, a veritable practical artillery manual. Titled Kitāb al-ʿIzz wa al-Manāfiʿ li al-Mujāhidīn fī Sabīl Allāh bi al-Madāfiʿ (The Book of Glory and Benefits for those who fight with Cannons on the Path of Allāh). The work was translated into Arabic in 1638 AD by a fellow Morisco Aḥmad ibn Qāsim ibn Shaykh al-Ḥajarī al-Andalusī (d.1642 AD). This work has a significant impact in the field of the firearms industry. The book contains superb engravings entirely consecrated to artillery, which includes content on European artilleries. The Andalusian artisans specialised in distinctive Western military techniques and contributed to their diffusion throughout the Islamic world to oppose their enemies. Due to the author’s background and experience, he was conscious of Euro-Christian superiority in artillery and the value of well-trained and instructed gunners. This article extracts from his work some significant exposition in this aspect. It represents a short account on the European source of firearm knowledge, a constituent of Islamic technology. The main objective of this research is to identify the European source on which the author relied. The methodology used in doing this research is library-based. The significance of this research is to shed light on the Andalusian efforts in transferring firearms know-how technology from the West to the East.